Implementasi Metode Syafa’ati dalam Pembelajaran Tahfidz di Pondok Pesantren Darul Ikhlas Marangkayu - Rafiatul Lathifah Septia Aini; Achmad Ruslan Afendi (Journal on Education, 2023)
The Darul Ikhlas Marangkayu Islamic Boarding School is the only Islamic boarding school in the 3T (foremost, outermost, lagging ) area which is located in the Marangkayu sub-district, and is labeled Nahdlatul Wathan (NW). The purpose of this research is to find out the application of the syafa'ati method in the Darul sincere Islamic boarding school. This research is a field research using descriptive qualitative method. This study uses observation, interviews, and documentation studies. The implementation of the syafa'ati method in Islamic boarding schools is divided into three stages, namely planning, implementing, and evaluating the syafa'ati method. This syafa'ati method is a method that focuses on the duration of memorization. With the provisions of the formula, namely B10x + H5x + U5x + D10x. The mushaf in the book of the syafa'ati method corresponds to a memorized mushaf (15 lines) accompanied by a translation, each page is divided into 3 hifzhoty which are marked with lines and verse numbers. Implementation of memorizing students are given a maximum of 30 minutes to memorize 1 hifdzoty. Then, when the students have successfully memorized 1 hifdzoty, the ustadz/ustadzah will give grades in the juz report cards that are available in the hifdzoty book